Growth of Marine Microalgae in Landfill Leachate and Their Ability as Pollutants Removal - Asma Liyana Shaari; Siti Norsyuhaila Che Sa; Misni Surif; Noorazah Zolkarnain; Razmah Ghazali (Tropical Life Sciences Research, 2021)
Leachate from landfill contains concentrated nutrients that may enter the terrestrial and aquatic environment, including nearby coastal areas. The nutrient contaminants eventually bring harm to marine organisms, including microalgae. This study was performed to investigate the growth of two green microalgal species, i.e. Chlorella sp. and Nannochloropsis sp. in diluted landfill leachate. Besides, the ability of nutrient removal by these microalgal was also explored from the changes of chemical oxygen demand (COD) and nutrients content. The initial and final concentrations of COD, NH3-N, and PO43- in the diluted leachate (5%, 10% and 15%) were measured and the growth patterns of these species were determined by counting the cell numbers for 12 days. Comparison of these microalgae showed that the growth rate of Nannochloropsis was significantly higher compared to Chlorella in all leachate concentrations. Leachate at 5% enhanced the growth of both microalgae, while leachates at 10% and 15% decreased their growth as early as at the beginning of the test. It is apparent that the less concentrated leachate discharged into seawater would not pose any toxicity to the environment and would not bear adverse effect to microalgae yet could promote their growth. This study also revealed that the microalgae could remediate leachate pollution by its ability of nutrient removal; thus, leading to the potential application in wastewater bioremediation, including industrial waste and palm oil mill effluent.